Heroic Collective Action: A People’s Blessing? - Bernauer, SJ, James (Studies in Christian-Jewish Relations, 2012)
Is the tendency to think of heroism as the activity of an individual rather than of a collective merely a matter of prejudice? Perhaps the European revolutions of 1989 and the Arab Spring of 2011 will foster more careful scrutiny of that assumption. Are the heroic figures so often featured in journalistic as well as historical accounts only individuals who are witnesses to a communal transformation and empowerment? Will a greater appreciation for heroic collective action promote a more nuanced perspective on the development of Jewish-Christian relations? The author proposes a shift of focus to communal heroism through an examination of four examples: the Yad Vashem project of recognizing the "Righteous among the Nations"; the Hungarian Revolution; the historical development of religious toleration; and, finally, the place that the Holocaust has taken on in contemporary reflection.